The Dependence of Urinary Bladder Responses on Extracellular Calcium Varies Between Muscarinic, Histamine, 5-HT (Serotonin), Neurokinin, Prostaglandin, and Angiotensin Receptor Activation - Phelps, Charlotte; Chess-Williams, Russ; Moro, Christian (Frontiers in Physiology, 2022)
With many common bladder diseases arising due to abnormal contractions, a greater understanding of the receptor systems involved may aid the development of future treatments. The aim of this study was to identify any difference in the involvement of extracellular calcium (Ca2+) across prominent contractile-mediating receptors within cells of the bladder lining. Strips of porcine urothelium and lamina propria were isolated from the urinary bladder dome and mounted in isolated tissue baths containing Krebs-bicarbonate solution, perfused with carbogen gas at 37°C. Tissue contractions, as well as changes to the frequency and amplitude of spontaneous activity were recorded after the addition of muscarinic, histamine, 5-hydroxytryptamine, neurokinin-A, prostaglandin E2, and angiotensin II receptor agonists in the absence and presence of 1µM nifedipine or nominally zero Ca2+ solution. The absence of extracellular Ca2+ influx after immersion into nominally zero Ca2+ solution, or the addition of nifedipine, significantly inhibited the contractile responses (p < 0.05 for all) after stimulation with carbachol (1µM), histamine (100µM), 5-hydroxytryptamine (100µM), neurokinin-A (300nM), prostaglandin E2 (10µM), and angiotensin II (100nM). On average, Ca2+ influx from extracellular sources was responsible for between 20-50% of receptor-mediated contractions. This suggests that although the specific requirement of Ca2+ on contractile responses was varied depending on the receptor, extracellular Ca2+ plays a key role in mediating G protein-coupled receptor contractions of the urothelium and lamina propria.